Adelaide Johnson papers - Johnson, Adelaide, 1859-1955.
Correspondence, diaries, speeches, articles, notes, and other papers concerning Johnson's life and activities as sculptor and feminist. Documents her work on the monument to Susan B. Anthony, Lucretia Mott, and Elizabeth Cady Stanton, now located in the crypt of the U.S. Capitol. Also includes records kept of sittings by Anthony, John Burroughs, Ella Wheeler Wilcox and others of whom she created portrait busts. Includes correspondence between Johnson and her husband, Alexander Frederick (Jenkins) Johnson, and other members of the Jenkins and Johnson families. Other correspondents include Susan B. Anthony, Lily Biedler, Arthur Brisbane, T. Campbell-Copeland, Edith M. Ferris, Helen H. Gardener, Agnes Hall, Gena R. Harding, Ida Husted Harper, Elizabeth Hale Falkner Murphy, Emmeline Pankhurst, Alice Paul, Cora L.V. Richmond, May Robson, Henry Rogers, May Wright Sewall, Helen L. Sumner, Emma Cecilia Thursby, Sara Carr Upton, and Henry G. Whitney.
Collection material in English.
Sculptor and suffragist. Born as Sarah Adeline Johnson.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anthony, Susan B. -- 1820-1906 -- Statues; Anthony, Susan B. -- 1820-1906 -- Correspondence; Biedler, Lily -- Correspondence; Brisbane, Arthur, -- 1864-1936 -- Correspondence; Burroughs, John, -- 1837-1921 -- Statues; Campbell-Copeland, T. -- Correspondence; Ferris, Edith M. -- Correspondence -- Correspondence; Gardener, Helen H. -- 1853-1925 -- Correspondence; Hall, Agnes -- Correspondence; Harding, Gena R. -- Correspondence; Harper, Ida Husted, -- 1851-1931 -- Correspondence; Johnson, Alexander Frederick -- Correspondence; Mott, Lucretia, -- 1793-1880 -- Statues; Murphy, Elizabeth Hale Falkner -- Correspondence; Pankhurst, Emmeline, -- 1858-1928 -- Correspondence; Paul, Alice, -- 1885-1977 -- Correspondence; Richmond, Cora L. V. -- 1840-1923 -- Correspondence; Robson, May, -- 1865-1942 -- Correspondence; Rogers, Henry -- Correspondence; Sewall, May Wright, -- 1844-1920 -- Correspondence; Stanton, Elizabeth Cady, -- 1815-1902 -- Statues; Sumner, Helen L. -- 1876-1933 -- Correspondence; Thursby, Emma Cecilia, -- 1845-1931 -- Correspondence; Upton, Sara Carr, -- 1843- -- Correspondence; Whitney, Henry G. -- Correspondence; Wilcox, Ella Wheeler, -- 1850-1919 -- Statues; Jenkins family; Jenkins family -- Correspondence; Johnson family; Johnson family -- Correspondence; United States Capitol (Washington, D.C.); Busts; Feminism; Monuments -- Washington (D.C.); Portrait sculpture; Sculpture; Sculptors; Suffragists